Emprego de planejamento experimental no desenvolvimento de métodos cromatográficos na indústria farmacêutica - Miglioranza, Bruna (Universidade Federal de São Carlos, 2012)
The aim of this study was to use experimental design techniques during the development and validation of high performance liquid chromatography (HPLC) methods for analysis of drugs in the pharmaceutical industry in order to demonstrate its applicability and benefits of its use. A multivariate assessment of the robustness of an assay method for vitamins of the B complex enabled the visualization of interactions between variables, which would not be possible through the univariate approach. A mixture design was performed for determining the extraction solvents of sesquiterpene lactones in pharmaceutical formulation containing arnica tincture. The mixture of solvents selected through the study allowed desirable extraction of compounds of interest from the sample, which was confirmed through the validation of the methodology. Finally, we conducted an exploratory planning on an analytical methodology for the determination of latanoprost, timolol maleate, preservatives and degradation product in eye drops. The design allowed the reduction of chromatographic run time and waste generation by about 44%.
Use of experimental design for the development of chromatographic methods in the pharmaceutical industry
Keywords: Cromatografia líquida; Cromatografia líquida de alta eficiência; Planejamento experimental; Análise multivariada; Mistura (Química); Planejamento de mistura; Avaliação multivariada da robustez; HPLC; Experimental planning; Mixture design; Multivariate robustness test; CIENCIAS EXATAS E DA TERRA::QUIMICA